THE CRITICAL LEVEL OF WATER INFILTRATION MAPPING IN GUNUNGPATI SUB-DISTRICTS, SEMARANG CITY - Budianta, Wawan; Septio, Ghenady; Setijadji, Lucas Donny (KURVATEK, 2024)
One of the reasons for the rapid population growth in the 21st century is urbanization. This leads to land degradation, which can result in a lack of water seeping into the ground when it rains in densely developed areas. Most of the water becomes surface runoff that cannot be absorbed by the soil because the runoff exceeds the soil's capacity to absorb water. In response to this situation, research was conducted on the criticality level of water catchment areas in Gunungpati District, Semarang City. The research involved collecting primary data through infiltration rates and lithology taken in the field, as well as secondary data, including information on land use and slope. This data was later verified in the area. The collected data were then analyzed using the Analytical Hierarchy Process (AHP) method by assigning weights to each parameter and sub-parameter. The parameters considered were land use, infiltration rate, slope, and lithology. The weighted values were overlaid to generate a critical level zoning map of water catchment areas in Gunungpati District, Semarang City. The critical level of water catchment areas in the research area can be categorized into "good" with an area of 1307.2 Ha, "normal natural" with an area of 1013.12 Ha, "starting to be critical" with an area of 436.26 Ha, "Slightly critical" with an area of 91.87 Ha, and "critical" with an area of 7.89 Ha, out of a total research area of 2856.34 Ha..